INFRASTRUKTUR DAKWAH DAN GERBANG MODERASI DI IBUKOTA BARU NEGARA REPUBLIK INDONESIA - Syamsuri Syamsuri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
The da'wah pillars in the city of Balikpapan stand parallel to the social establishment system. Population dynamics move in line with the development of the oil and gas mining industry. The anniversary of the city of Balikpapan which is commemorated every year begins with the momentum of oil drilling for the first time at Mount Balikpapan on February 10, 1897. The spirit of preaching amar makruf nahi munkar continues to be encouraged in anticipation of changes in the Muslim faith, due to the development of the oil refinery industry. The phenomenological method in the perspective of Islamic activities in the city of Balikpapan, there is a phenomenon of preaching infrastructure that has deviated from the strength of the two sultanates, namely the Kingdom of Paser and the Kingdom of Kutai Kartanegara Ing Martapura. DKI Province (Special Capital Region) Jakarta, which since independence until now as the State Capital (IKN), was formerly known as Jayakarta. Now, DKI will move towards the IKN. From Jakarta to the Kartanegara